The Effect of Three Different Suture Anchors for Rotator Cuff Repair on Primary Cultures of Human Bone Marrow Mesenchymal Stem Cells - Thiébat, Gabriele; Capitani, Paolo; de Girolamo, Laura; Perucca Orfei, Carlotta; Facchini, Francesca; Schoenhuber, Herbert; Viganò, Marco (Joints, 2018)
Purpose The purpose of this study is to investigate the in vitro biocompatibility of three different suture anchors (all-suture anchor, metal anchor, and polyetheretherketone anchor), commonly used for the rotator cuff repair.Methods To assess the biocompatibility of the anchors, the possible cytotoxicity and the immunogenicity of the devices were assessed by cell viability assay and cell count on cultures of bone marrow stem cells (BMSCs) and peripheral blood leucocytes (PBLs), respectively. The possible inhibitory effect of the devices on BMSCs osteogenic potential was evaluated by alkaline phosphatase activity and matrix deposition assay.Results The viability of BMSCs was slightly reduced when cultured in the presence of the devices (−24 ± 3%). Nevertheless, they were able to differentiate toward the osteogenic lineage in all culture conditions. The proliferation of PBLs and the production of interleukin-2 were not enhanced by the presence of any device.Conclusion The analyzed devices did not significantly affect the normal cells functions when directly cultured with human primary BMSCs or PBLs, in terms of osteogenic differentiation and inflammatory reaction.Clinical Relevance A deeper knowledge of the biological reactions to different devices used in rotator cuff surgeries would improve the clinical outcome of these procedures.
Keywords: rotator cuff; suture anchors; bone marrow stem cells; biocompatibility; culture